2007
DOI: 10.1038/sj.pcan.4500990
|View full text |Cite
|
Sign up to set email alerts
|

Dutasteride significantly improves quality of life measures in patients with enlarged prostate

Abstract: The purpose of this study was to determine the effect of dutasteride on quality of life of men with lower urinary tract symptoms associated with enlarged prostate or benign prostatic hyperplasia (BPH) as measured by symptom problem index (SPI), BPH-specific interference with activities (BSIA), BPH-specific psychological well-being (BPWB) and BPH-specific lifestyle adaptations (BSLA). Data were derived from three randomized, double-blind studies conducted in 4325 men treated with placebo or dutasteride (0.5 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…The current standard therapy for bothersome BPH/LUTS is ␣ 1 -adrenergic antagonist (␣-blocker) and antiandrogenic 5␣-reductase inhibitor, targeting the dynamic and static components, respectively (52,55). Although effective, these drugs may be associated with unwanted side effects, including dizziness, hypotension, and sexual dysfunction, which may be exacerbated by combination therapy (41).…”
mentioning
confidence: 99%
“…The current standard therapy for bothersome BPH/LUTS is ␣ 1 -adrenergic antagonist (␣-blocker) and antiandrogenic 5␣-reductase inhibitor, targeting the dynamic and static components, respectively (52,55). Although effective, these drugs may be associated with unwanted side effects, including dizziness, hypotension, and sexual dysfunction, which may be exacerbated by combination therapy (41).…”
mentioning
confidence: 99%
“…They reported that combination therapy significantly improved disease‐specific HRQoL when compared with each monotherapy. Two other studies assessed the effectiveness of dutasteride over 24 weeks, and both reported dutasteride to significantly improve HRQoL in patients with BPH (Desgrandchamps et al ., ; O'Leary et al ., ). It is interesting to note that the study conducted by O'Leary et al .…”
Section: Resultsmentioning
confidence: 97%
“…Seven studies evaluated the effect of medical therapy on the HRQoL of men with BPH. The study designs were RCT ( n = 3), descriptive comparative studies ( n = 4), and descriptive correlational ( n = 1) (Barkin et al ., ; Desgrandchamps, Droupy, Irani, Saussince, & Comenducci, ; Fourcade et al ., ; Höfner et al ., ; Komiya et al ., ; Montorsi et al ., ; O'Leary, Roehrborn, & Black, ; Suzuki et al ., ). All studies reported significant improvements in HRQoL following medical therapy, except one study by Fourcade et al .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Androgens play a key role in prostate development, maturation, homeostasis, and pathogenesis including benign prostatic hyperplasia (BPH) and prostate cancer [1][2][3][4]. Androgen action is mediated through the androgen receptor (AR), a ligand-regulated transcription factor that regulates the expression of many androgen-responsive genes [5,6].…”
Section: Introductionmentioning
confidence: 99%